qual a resposta dessa equacao
Anexos:
![](https://pt-static.z-dn.net/files/d4d/38744061fd9ccde61c704df33d1e1aa3.jpg)
Soluções para a tarefa
Respondido por
0
x - ( x + 1) = 12 - 3x - 2
x - x - 1 = 12 - 3x -2 x e -x se anulam
-1 = 12 - 3x - 2
-1 - 12 + 2 = - 3x
- 11 = - 3x
x = -11/-3
x = 11/3
x - x - 1 = 12 - 3x -2 x e -x se anulam
-1 = 12 - 3x - 2
-1 - 12 + 2 = - 3x
- 11 = - 3x
x = -11/-3
x = 11/3
Respondido por
0
x-(x+1)=12-3x-2
x-x+3x=12+2+1
3x=15
x=15/3
x=5
x-x+3x=12+2+1
3x=15
x=15/3
x=5
Perguntas interessantes
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Saúde,
1 ano atrás
Artes,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Filosofia,
1 ano atrás